2010
DOI: 10.1002/pds.1991
|View full text |Cite
|
Sign up to set email alerts
|

Description of hypersensitivity adverse events following administration of heparin that was potentially contaminated with oversulfated chondroitin sulfate in early 2008

Abstract: Intravenous administration and a higher OSCS concentration appeared to correlate with a more rapid onset of event. The FDA continues to monitor AEs associated with heparin use and has taken appropriate regulatory action to ensure a safe heparin drug supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 12 publications
0
46
0
1
Order By: Relevance
“…In this regard the crucial anticoagulant drug heparin is a representative example due to several cases of heparin adulteration leading to numerous adverse reactions and death in 2007-2008 [47]. This has demonstrated that necessity of the development of new method for analysis of heparin origin.…”
Section: Discussionmentioning
confidence: 98%
“…In this regard the crucial anticoagulant drug heparin is a representative example due to several cases of heparin adulteration leading to numerous adverse reactions and death in 2007-2008 [47]. This has demonstrated that necessity of the development of new method for analysis of heparin origin.…”
Section: Discussionmentioning
confidence: 98%
“…Another example is that of polymeric DPs in aminopencillins that have been attributed to cause allergenicity and not the drugs themselves [6,7]. The most recent case is the presence of oversulfated chondroitin sulfate in heparin samples that caused allergenic reactions and over 100 deaths [8]. A subset of IMPs and DPs even carry potential for genotoxicity, which pose an additional safety concern, because these molecules can cause genetic mutations, chromosomal breaks, and/or chromosomal rearrangements, leading to significant risk for carcinogenicity or other toxic effects [9].…”
Section: The Focus On Impurities and Degradation Productsmentioning
confidence: 98%
“…Ïîìèìî ñïåöèôè÷åñêîãî àíòèêîàãóëÿíòíîãî äåéñò-âèÿ, ÷ðåçâû÷àéíî âàaeíîé ïðîáëåìîé ÿâëÿåòñÿ îáåñïå-÷åíèå ïðèåìëåìîãî óðîâíÿ èììóíîãåííîñòè ïðåïàðà-òîâ ãåïàðèíà, êîòîðàÿ ìîaeåò ñòàòü ïðè÷èíîé ðàçâèòèÿ íåaeåëàòåëüíûõ ðåàêöèé (ãåïàðèí-èíäóöèðîâàííàÿ òðîìáîöèòîïåíèÿ) è ñíèaeåíèÿ ýôôåêòèâíîñòè ïðåïà-ðàòîâ ãåïàðèíà [13,15]. Èììóíîãåííîñòü îïðåäåëÿåò-ñÿ ìíîaeåñòâîì ôàêòîðîâ, ñðåäè êîòîðûõ ìîãóò áûòü âàðèàíòû ãëèêîçèëèðîâàíèÿ, êà÷åñòâåííûé è êîëè÷å-ñòâåííûé ñîñòàâ ïðèìåñåé, îñîáåííîñòè ëåêàðñòâåí-íîé ôîðìû, óñëîâèÿ åå õðàíåíèÿ è ñïîñîá ïðèìåíåíèÿ ïðåïàðàòà.…”
Section: ââåäåíèåunclassified